A phase 3, multi-center, multinational, randomized, double-blind, placebo-controlled study to evaluate the efficacy and safety of levofloxacin inhalation solution (APT-1026) in stable cystic fibrosis patients - Flume, Patrick; VanDevanter, Donald R.; Morgan, E.E.; Dudley, Michael N.; Loutit, Jeffery S.; Bell, Scott C.; Kerem, Eitan; Fischer, R.; Smyth, Alan R.; Aaron, Shawn D.; Conrad, Douglas; Geller, David E.; et al. (Elsevier, 2016)
Rationale